A multicentre real-life prospective cohort study on effectiveness, durability and safety of long-acting injectable cabotegravir and rilpivirine in northern Italy: the LONGITUDE study - Mazzitelli, Maria; Cozzolino, Claudia; Yaacoub, Dina; Pieri, Angela; Erne, Elke; Puzzolante, Cinzia; Fontana, Beatrice; Giglia, Maddalena; Rigamonti, Claudio; Cordioli, Maddalena; Zanchi, Chiara; Fasani, Giada; et al. (Journal of antimicrobial chemotherapy, 2025)
We herein present a prospective multicentre experience of long-acting injectable (LAI) cabotegravir/rilpivirine from 11 different HIV clinics in northern Italy, focusing on the regimen's effectiveness, durability and safety in a real-life setting. We included all people who received at least one dose of LAI cabotegravir/rilpivirine, recording clinical data, and assessing factors associated with treatment discontinuation (TD) for any cause. Kaplan-Meier curves were used to estimate the probability of TD, and Cox regression models identified significant predictors of TD. A sub-analysis was conducted focusing on TD due to virological failure (VF, defined as two consecutive HIV-RNA values >200 copies/mL or a single value over 200 copies/mL leading to treatment withdrawal). We included 483 participants (81.6% males) with a median age of 49 (IQR: 40-58) years. In 74.1% of participants, the LA regimen was started by choice, with 51.8% coming from a dual oral antiretroviral regimen. During a median follow-up time of 22 (IQR: 13-26) months, 54 (11.1%) participants had TD (incidence = 0.627 per 100 person-months of follow-up), mostly due to side effects (31, 6.4%) but with 7 (1.4%) due to VF [with people reporting major integrase strand transfer inhibitor (INSTI) and NNRTI resistance mutations in 71.4% cases]. When multivariable analysis was performed, age, years with HIV, CD4/CD8 ratio and BMI were significantly associated with TD. Also, we detected that the number of previous antiretroviral regimens was significantly associated with VF. Despite the overall effectiveness, TD was observed in a specific subset of people, primarily due to side effects, with a smaller proportion experiencing VF. Factors associated with both TD and VF underscore the importance of personalized selection to optimize LAI cabotegravir/rilpivirine outcomes and to improve regimen persistence.